Between semiotic linguistics and narratology: Objective grounding and similarity in essayistic translation - Goethals, Patrick (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
In memoriam Christophe Halsberghe In this article, I will show how the description of meaning in translated texts can be enriched by combining insights from semiotic linguistics and narratology. Concretely, I will focus on the phenomenon of ‘grounding’ as it is described in Cognitive Grammar. Special attention will be paid to ‘ob-jective grounding’. I will claim that this phenomenon plays a central role in essayistic translation, as it reflects one of the core characteristics of this type of translation, i.e. the search for similarity. The analysis of objective grounding will allow us to develop this notion, describing similarity at product level but also at the communicative process level. In the final sec-tion, I will try to link the search for similarity with psychological notions such as empathy and anxiety.